PTH-326 Cytoreductive surgery and heated intraperitoneal chemotherapy with synchronous liver resection for metastases of colorectal origin. (22nd June 2015) - Fish, R; Deshpande, R; Aziz, O; Fulford, P; Renehan, A; Wilson, M; O'Dwyer, S
Abstract : Introduction: The combination of peritoneal metastases (PMCR) and liver metastases in colorectal cancer (CRLM) has been considered a relative contra-indication to surgical treatment of either lesion. In the UK joint resection has not been widely undertaken and there is no published UK data. We present a cohort of eight synchronous liver resections with cytoreduction and heated intraperitoneal chemotherapy (CRS+HIPEC) at a single UK centre. Method: All patients undergoing CRS+HIPEC with a hepatobiliary surgeon were identified from the prospectively kept PTS database. Patients who had only liver mobilisation were excluded. Outcome data was gathered from the electronic patient record and the PTS database. Post-hepatectomy liver failure was defined using International Study Group of Liver Surgery criteria. Results: Seven patients underwent eight CRS+HIPEC procedures with synchronous liver resection for metastasis of colorectal origin over 5 years. Median PCI was 9 (range 3–17), with CC-0/1 resection in all patients. The median volume of resected liver was 90.6 cm 3 (2760 cm 3 – 15 cm 3 ). Median CCU stay was 2 (1–3) days and hospital stay 11 (8–20) days. Two patients experienced grade 3–4 complications: one grade-A post-hepatectomy liver failure and one sepsis. There was no 30 day mortality. Median CCU stay, inpatient stay, and grade 3–4 complication rate for patients undergoing CRS+HIPEC without liver resection for PMCR (n = 85) in our unit is 2 (0–16) days 12 (4–141) days and 21% respectively. Three patients are alive at a median follow-up of 59.2(39–61) months. All surviving patients had CC0 resections and PCI <11. Median overall survival is 36.9 months. Conclusion: In selected patients with metastatic colorectal cancer, synchronous liver resection with CRS+HIPEC is safe, with inpatient stay, CCU stay and complication rates comparable to CRS+HIPEC without liver resection in our unit. Our outcomes and survival figures are consistent with published data which suggests improved overall survival compared to modern systemic chemotherapy. Disclosure of interest: None Declared.